Implementation of Real Time Brainwave Visualisation and Characterisation - Suresh Manic, K.; Aravind, C.V.; Saadha, A.; Pirapaharan, K. (Journal of Engineering Science and Technology, 2015)
Human brain is the most complex organ in the body which controls all conscious and unconscious aspects of the body. Numerous neurons combine together to make up the brain and gives us the power of speech, imagination and logical thinking. The communication between these neurons create magnetic and electric field that can be measured through an Electroencephalograph. These measured brainwaves consist of component bandwidths categorised based on their frequency. Studies have shown that the presence of these waves in the brainwave depend on the emotional and mental status of the person as well as physical and mental actions that are being carried out. This paper looks into the different aspects of acquiring these brainwaves in real time and conditioning the waves in order to remove unwanted artefacts for digitisation and signal analysis. An in depth study is carried out for obtaining the waves through a data acquisition device DAQ 6009 and the categorisation of the brainwave to different components through the software platform LABVIEW. Studies are then conducted to analyse the brainwaves during different conditions to create a database of what a brainwave constitute of at a particular activity. A standalone modular unit is developed that could be used to acquire; store and analysis the brain wave signal in real time and is tested for its performance.
Keywords: Brain signal visualisation; Characterisation; Portable model